An assessment of employment opportunities created by the Keiskamma Irrigation Scheme - Nightingale, Fiona Mary (Rhodes University, Faculty of Science, Department of Geography, 1983)
Preface: "The need for development as observed today is a problem peculiar to the 20th century. The current situation is characterised by the fact that there are no more empty places on the earth, while our use of dwindling resources is curbed by environmental constraint." (Mouly and Costa, 1974, 155). The need for development is not equally felt by all nations as disparities in income and standards of living on a national basis have dissected the world into developed and underdeveloped countries. Disparities also exist within nations. These divisions are not simply determined nor are the terms related to development clearly defined - a matter that will be discussed in Chapter Two. Impetus to developing underdeveloped countries may be provided by various means, such as a general injection of capital or by more specific development projects. The purpose of these projects is to initiate changes that are intended to promote rapid development of an area. An interest has been shown by Geographers in the ability of these projects to stimulate economic growth in surrounding areas (Silberfein, 1976). The resulting success of development projects is closely related, if not determined, in large measure, by the aims. In view of the need for the aims of development projects to be successfully fulfilled, research into what constitute constructive developmental aims would be beneficial. Previous studies have revealed problems encountered with conflicting aims and objectives (Mountjoy, 1971); poorly defined aims (de Wilde, 1967); and inadequate groundwork prior to initiating the project (Berry, 1976). It is the intention of the study to examine the impact made by a development project in an underdeveloped area, and thereby assess the extent to which the development aims have been carried out. In order to carry out an examination of a development project in an underdeveloped area, an area in need of development had to be selected; a project within the area chosen for study; and the particular aim of the project examined. The Ciskei, a Homeland in South Africa, was chosen as a suitable area for study. A number of factors contribute towards it being an area in need of development, particularly as the Ciskei is a small country and dependent on South Africa, which is explained in the overview of the Ciskei in Chapter One. Three characteristics of underdevelopment noted by Seers (1972) are poverty, inequality and underemployment. Of these three factors it was decided to focus on unemployment as the indication of the extent to which development has taken place. The reduction of unemployment was one of the aims of the Keiskammahoek Irrigation Scheme, the project chosen for study. The overview concludes with a presentation of the Keiskamma Irrigation Scheme.
Keywords: Economic development projects -- South Africa --Ciskei; Job creation -- South Africa -- Ciskei; Irrigation -- South Africa -- Ciskei; Agriculture -- Economic aspects -- South Africa -- Ciskei; Black people -- Employment -- South Africa -- Ciskei